Anna-Teresa Tymieniecka’s Philosophy of Life and the Question of God - Mruszczyk, Magdalena (Folia Philosophica, 2021)
Anna-Teresa Tymieniecka’s philosophy of life of is a phenomenological vision of the self-development of the human spirit presented from a cosmological perspective and in the formula of self-individualization of man in existence and at the same time his self-interpretation in life. This development cannot be realized solely on the basis of reason, through the subject’s cognitive act. For the self-interpretation of man in existence, his creative act is necessary, one which expresses the creative operation of the human imagination. It is this path of the human mind’s self-tracking which sees its sources in the first, pre-organic processes of the formation of the universe. These processes evolved towards the attainment of an ever higher degree of complexity in the living forms of nature, up to the form of human self-awareness expressed in man’s creative act and in the realization by the human spirit of its transnatural vocation. Man’s aspiration to fulfill his life’s destiny takes place in three steps (or “movements of the soul”): intellectual, socio-moral, and sacred. Their description in the phenomenology of life emerges from a metaphysical and at once existentialist vision of human life as being in-unity-with-all-that-lives. We can say that this vision is the starting point of Tymieniecka’s phenomenology of life and of the human creative condition. Arguably, in her theory, the most important thing is to follow the sacred path of life’s logos in order to attain communion with the Divine (God, the Sacred, the Transcendent, the Unconditioned, the All-Encompassing). On this path, the phenomenology of the human spirit attains completion and phenomenology – phenomenology.